Bone Marrow Infiltration in Rosai–Dorfman Disease - Fatima Zahra Rahali; Fatima Taher; Houda Nassih; Sanae Sayagh (Case Reports in Hematology)
Rosai–Dorfman disease (RDD) is a rare and benign nonLangerhans cell histiocytosis. RDD commonly affects children and young adults typically presenting with massive, painless, and bilateral cervical lymphadenopathy. Extranodal involvement is present in about 40% of cases, and bone marrow infiltration is rare and unusual. RDD prognosis is usually good, however, involvement of bone marrow is associated with poor prognosis. We report a case of RDD with bone marrow involvement occurring in a 5-year-old female. She was admitted for asthenia, gingival bleeding, and diffuse bone pain without fever. Physical examination showed pallor, petechiae over the abdomen, painless and bilateral cervical lymphadenopathy, and several bony nodules, without splenomegaly or hepatomegaly. Cell blood count revealed microcytic hypochromic anemia with thrombocytopenia. Bone marrow aspiration showed infiltration by large histiocytes with hypochromatic nuclei and abundant vacuolated cytoplasm without emperipolesis. Biopsies of bone marrow, lymph node, and bone revealed immunohistochemical features of RDD: the histiocytes were positive for CD68 and S100 protein, but negative for CD1a. The patient initially received symptomatic treatment. One week after admission, she died of septic shock before the final establishment of RDD diagnosis. This case report highlights that bone marrow involvement in RDD is rare and associated with poor prognosis. We also aim to emphasize the obligation of bone marrow exploration in patients with RDD and presenting cytopenias in order to make an early diagnosis of bone marrow infiltration.